Το ChatGPT στην ελληνική ανώτατη εκπαίδευση: Εξερευνώντας απόψεις και προτείνοντας ένα διδακτικό σενάριο - Κarakiza Tsampika; Sidiropoulou, Anthi (Ανοικτή Εκπαίδευση: το περιοδικό για την Ανοικτή και εξ Αποστάσεως Εκπαίδευση και την Εκπαιδευτική Τεχνολογία, 2025)
The research objective is twofold. Primarily, the implementation of an educational scenario for the familiarization and critical use of an AI tool. Secondly, to explore students’ views and attitudes towards ChatGPT. Free association and conceptual map construction techniques were used to capture the participants’ attitudes. Thirty-five students participated in the study and research material was collected implementing an educational scenario when the participants logged into the ChatGPT environment. The material was processed using qualitative content analysis and conceptual map observation tools. Some of the most important findings were the lack of Greek students’ previous experience with AI tools, yet their quick familiarisation with the environment. The students identified significant shortcomings in the environment, such as lack of internal coherence and “colourless”, converged discourse. The training scenario allowed them to check the reliability of the generated information and to move from the initial impression of technological “objectivity” to more realistic perceptions of ChatGPT’s contributions. Such research is considered particularly useful as AI tools are now easily accessible and used by students during their academic life. Therefore, critical evaluation skills and a holistic understanding of the AI framework are essential for their more effective integration into academic processes and contemporary life in general.